Fire and collapse: Untangling the formation of destruction layers using archaeomagnetism. Issue 5 (7th January 2018) - Shahack‐Gross, Ruth; Shaar, Ron; Hassul, Erez; Ebert, Yael; Forget, Mathilde; Nowaczyk, Norbert; Marco, Shmuel; Finkelstein, Israel; Agnon, Amotz
Abstract: Historical events are sometimes expressed in destruction layers. We present here a study in which aspects of construction, destruction, and chronostratigraphy of fired mud bricks were explored using archaeomagnetism, infrared spectroscopy, and micromorphology. We measured 88 oriented samples mostly collected from one stratum, dated ca . 1000 B.C.E., representing a destroyed late Canaanite (late Iron Age I) city in Tel Megiddo, Israel. Firing temperatures, evaluated from infrared spectroscopy, micromorphology, and high‐temperature magnetic susceptibility cycles, range between 300°C and 800°C. Samples studied in one archaeomagnetic site yield a single stable magnetization vector in demagnetization experiments. Archaeomagnetic site means of three standing walls are grouped near the expected direction of the ancient geomagnetic field. We propose that walls in the destruction layer were constructed from sun‐dried mud bricks that later burned during the destruction. Collapsed bricks and tilted walls show variable directions, diagnostic for the relative timing of collapse and cooling of bricks, during and following the destruction event. In addition, we attempt to assign stratigraphic affiliation based on archaeomagnetic considerations to standing walls, which are spatially disconnected from the studied destruction layer. Altogether, this study demonstrates the usefulness of archaeomagnetism to understanding site formation processes related to fire and destruction.